1982
DOI: 10.1042/cs0630533
|View full text |Cite
|
Sign up to set email alerts
|

The Antidiuretic Effect of Chronic Hydrochlorothiazide Treatment in Rats with Diabetes Insipidus: Renal Mechanisms

Abstract: 1. Brattleboro rats with hereditary diabetes insipidus were maintained in metabolism cages for 12-14 days. During the final 5-7 days hydrochlorothiazide was added to the food of half the animals, resulting in a sustained antidiuresis. At the end of this time all rats were anaesthetized and their renal function was investigated.2. Water, sodium and potassium excretion rates during anaesthesia were similar to their respective values during the final period in metabolism cages.3. Total glomerular filtration rate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

1983
1983
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 14 publications
1
23
0
Order By: Relevance
“…Previously, the osmolality of renal papillary interstitial fluid from HCTZ-treated Brattleboro rats was shown to be considerably greater than that from untreated animals, accompanied by a significant increase in sodium concentration (9). In this study, the abundance of NCC in distal convoluted tubule was not altered by Li administration but increased by HCTZ treatment in Li-induced NDI rats.…”
Section: Hctz Treatment Upregulates Ncc and Enac In Liinduced Ndimentioning
confidence: 48%
See 1 more Smart Citation
“…Previously, the osmolality of renal papillary interstitial fluid from HCTZ-treated Brattleboro rats was shown to be considerably greater than that from untreated animals, accompanied by a significant increase in sodium concentration (9). In this study, the abundance of NCC in distal convoluted tubule was not altered by Li administration but increased by HCTZ treatment in Li-induced NDI rats.…”
Section: Hctz Treatment Upregulates Ncc and Enac In Liinduced Ndimentioning
confidence: 48%
“…However, Shirley et al (9) showed that the mechanism of sustained antidiuresis during chronic HCTZ administration in DI differs from that of the acute response. When they recorded distal delivery and urine flow simultaneously during chronic thiazide antidiuresis, the allover change in distal delivery (Ϫ15%) or the enhanced proximal solute and water reabsorption was considered to be too small to account for the profound antidiuresis.…”
Section: Hctz Treatment Partially Reverses Li-induced Aqp2 Downregulamentioning
confidence: 99%
“…the LE rats in experiment 1) rmP induced a small diuresis, which was converted into an antidiuresis in the absence (or suppression) of circulating vasopressin. These findings are reminiscent of the paradoxical, and still not completely understood, antidiuretic effect of thiazide diuretics in diabetes insipidus (26,27).…”
Section: Discussionmentioning
confidence: 90%
“…Following micropuncture, the kidney papilla was excised and a sample of papillary interstitial fluid obtained (Shirley, Walter & Laycock, 1982). Although urine osmolality was lower in thiazide-treated rats than in control animals (1377+64 vs. 1885 + 150 m-osmole/kg H20, P < 0 005), papillary fluid osmolality in the two groups was similar (thiazide group: 1867 + 162; control group: 1732 + 106 m-osmole/ kg H20).…”
Section: Pmentioning
confidence: 99%